Impacts of an intense wildfire smoke episode on surface radiation, energy and carbon fluxes in southwestern British Columbia, Canada - McKendry, Ian G.; Christen, Andreas; Lee, Sung-Ching; Ferrara, Madison; Strawbridge, Kevin B.; O'Neill, Norman; Black, Thomas Andrew (2019)
Abstract: A short, but severe, wildfire smoke episode in July 2015, with an aerosol optical depth (AOD) approaching 9, is shown to strongly impact radiation budgets across four distinct land-use types (forest, field, urban and wetland). At three of the sites, impacts on the energy balance are also apparent, while the event also appears to elicit an ecosystem response with respect to carbon fluxes at the wetland and a forested site. Greatest impacts on radiation and energy budgets were observed at the forested site where the role of canopy architecture and the complex physiological responses to an increase in diffuse radiation were most important. At the forest site, the arrival of smoke reduced both sensible and latent heat flux substantially but also lowered sensible heat flux more than the latent heat flux. With widespread standing water, and little physiological control on evapotranspiration, the impacts on the partitioning of turbulent fluxes were modest at the wetland compared to the physiologically dominated fluxes at the forested site. Despite the short duration and singular nature of the event, there was some evidence of a diffuse radiation fertilization effect when AOD was near or below 2. With lighter smoke, both the wetland and forested site appeared to show enhanced photosynthetic activity (a greater sink for carbon dioxide). However, with dense smoke, the forested site was a strong carbon source. Given the extensive forest cover in the Pacific Northwest and the growing importance of forest fires in the region, these results suggest that wildfire aerosol during the growing season potentially plays an important role in the regional ecosystem response to smoke and ultimately the carbon budget of the region